Probability-based preservational variations within the early Cambrian Chengjiang biota (China) - Farid Saleh; Xiaoya Ma; Pauline Guenser; M. Gabriela Mángano; Luis A. Buatois; Jonathan B. Antcliffe (PeerJ, 2022)
The Chengjiang biota (Yunnan Province, China) is a treasure trove of soft-bodied animal fossils from the earliest stages of the Cambrian explosion. The mechanisms contributing to its unique preservation, known as the Burgess Shale-type preservation, are well understood. However, little is known about the preservation differences between various animal groups within this biota. This study compares tissue-occurrence data of 11 major animal groups in the Chengjiang biota using a probabilistic methodology. The fossil-based data from this study is compared to previous decay experiments. This shows that all groups are not equally preserved with some higher taxa more likely to preserve soft tissues than others. These differences in fossil preservation between taxa can be explained by the interaction of biological and environmental characteristics. A bias also results from differential taxonomic recognition, as some taxa are easily recognized from even poorly preserved fragments while other specimens are difficult to assign to higher taxa even with exquisite preservation.